DIVORCE CLAIM TEXT AT RELIGIOUS COURT OF PRAYA: SYSTEMIC FUNCTIONAL LINGUISTIC STUDY - Wirajayadi, Lalu (International Journal of Systemic Functional Linguistics, 2017)
Abstract This research reports description of modality system and its relevance toward discourse learning at higher education. The approach used in this research was qualitative descriptive with the orientation of Systemic Functional Linguistics (SFL) theory. The data collection method was documentation and note-taking technique. The data analysis was done by using identification technique. The result of data analysis was presented by using description of phrases and clauses. The finding of the research showed that the system of modality in Divorce Claim text consists of the clauses that are organized as modalization (probability and frequency) 18 (15.51%) and modulation (necessity and tendency) 16 (13.80%) as an effort to strengthen the idea, view, and opinion to convince the judge in deciding a case that would be decided related to the content of the claim that had been submitted. Keywords: Text, Modality, LFS, Learning